Physiological and performance effects of dietary nitrate and N-acetylcysteine supplementation during prolonged heavy-intensity cycling. Issue 23 (2nd December 2022) - Tan, Rachel; Black, Matthew; Home, Joseph; Blackwell, Jamie; Clark, Ida; Wylie, Lee; Vanhatalo, Anni; Jones, Andrew M.
ABSTRACT: The purpose of this study was to investigate effects of concurrent and independent administration of dietary nitrate (NO3 − ), administered as NO3 – -rich beetroot juice (BR; 12.4 mmol of NO3 − ), and N-acetylcysteine (NAC; 70 mg·kg −1 ) on physiological responses during prolonged exercise and subsequent high-intensity exercise tolerance. Sixteen recreationally active males supplemented with NO3 – -depleted beetroot juice (PL) or BR for 6 days and ingested an acute dose of NAC or maltodextrin (MAL) 1 h prior to performing 1 h of heavy-intensity cycling exercise immediately followed by a severe-intensity time-to-exhaustion (TTE) test in four conditions: 1) PL+MAL, 2) PL+NAC, 3) BR+MAL and 4) BR+NAC. Pre-exercise plasma [NO3 − ] and nitrite ([NO2 − ]) were elevated following BR+NAC and BR+MAL (both P < 0.01) compared with PL+NAC and PL+MAL; plasma [cysteine] was increased in PL+NAC and BR+NAC (both P < 0.01) compared to PL+MAL. Muscle excitability declined over time during the prolonged cycling bout in all conditions but was better preserved in PL+NAC compared to BR+NAC ( P < 0.01) and PL+MAL ( P < 0.05). There was no effect of supplementation on subsequent TTE . These findings indicate that co-ingestion of BR and NAC does not appreciably alter physiological responses during prolonged heavy-intensity cycling or enhance subsequent exercise tolerance.